2004
DOI: 10.1074/jbc.m402282200
|View full text |Cite
|
Sign up to set email alerts
|

The Muscle-specific Calmodulin-dependent Protein Kinase Assembles with the Glycolytic Enzyme Complex at the Sarcoplasmic Reticulum and Modulates the Activity of Glyceraldehyde-3-phosphate Dehydrogenase in a Ca2+/Calmodulin-dependent Manner

Abstract: The skeletal muscle specific Ca 2؉ /calmodulin-dependent protein kinase (CaMKII␤ M ) is localized to the sarcoplasmic reticulum (SR) by an anchoring protein, ␣KAP, but its function remains to be defined. Protein interactions of CaMKII␤ M indicated that it exists in complex with enzymes involved in glycolysis at the SR membrane. The kinase was found to complex with glycogen phosphorylase, glycogen debranching enzyme, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and creatine kinase in the SR membrane. CaMKI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
68
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 44 publications
2
68
0
Order By: Relevance
“…After sonication for 4 separate periods of 30 seconds at 200 W on ice, the suspensions were centrifuged at 20,000 Â g for 10 minutes, and the supernatants were saved. Activities of phosphofructokinase (PFK), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and pyruvate kinase (PK) were determined by monitoring changes in absorbance at 340 nm as described previously (5,30,31).…”
Section: Assays For Activities Of Glycolytic Enzymes and Western Blotmentioning
confidence: 99%
“…After sonication for 4 separate periods of 30 seconds at 200 W on ice, the suspensions were centrifuged at 20,000 Â g for 10 minutes, and the supernatants were saved. Activities of phosphofructokinase (PFK), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and pyruvate kinase (PK) were determined by monitoring changes in absorbance at 340 nm as described previously (5,30,31).…”
Section: Assays For Activities Of Glycolytic Enzymes and Western Blotmentioning
confidence: 99%
“…Data also suggest that ␣KAP along with the novel CaMKII␤ 4 are enriched in cardiac SR membranes, implying a common regulatory role for these molecules in these two muscle types (13)(14)(15). Further, studies suggest that CaMKII␤ 4 can recruit the glycolytic machinery to the SR membrane in cardiac and skeletal muscle and potentially serve to spatially modulate the supply of ATP for the calcium transport process (13,14). In view of the emerging concept of spatial and temporal control of signal transduction through kinase-anchoring proteins, we investigated further the role of ␣KAP at the SR membrane and found that it directly interacts with the calcium ATPase and serves to recruit CaMKII isoforms and modulate the phosphorylation of PLN at Thr-17, which is known to critically regulate calcium uptake and muscle relaxation (18).…”
mentioning
confidence: 79%
“…Data also suggest that ␣KAP along with the novel CaMKII␤ 4 are enriched in cardiac SR membranes implying a common regulatory role for these molecules in these two muscle types (13)(14)(15). Further, studies suggest a significant level of a muscle-specific CaMKII ␤ isoform (CaMKII␤ 4 ) in cardiac and skeletal muscle (14 -16).…”
mentioning
confidence: 86%
See 2 more Smart Citations